Analys av seismisk aktivitet vid malmkroppen Fabian - Andersson, Fredrik (2013)
In Malmberget LKAB have approximately 20 different ore bodies, but not allof them are mined in the present. With time mining continues further deeperand rock mechanics related problems are increasing. When rock stress exceedsthe rock mass strength potential and stored energy is released and radiated asseismic energy. The mining activities are affecting a larger area around the orebodies and the secondary stresses can affect the normal stress over a joint orstructure in a negative way and may cause a sliding that also radiates seismicenergy.The seismic event can be divided into two main groups, compressive stressinduced events and slippages. The first category includes different types ofrock bursts and the second category includes different types of shear failures.To monitor seismic events in the rock mass, the same instrumentation as forearthquake monitoring is used. The monitoring system consists of a number ofgeophones, connected in a network, which detects movements in the rockmass.This study includes an analysis of seismic events located in the vicinity of theFabian ore body. The first part of the study focuses on differences in theseismic signature between different mining levels and periods.In the second part of the analysis the events are related to blasting and muckingin the production process. The purpose with this part was to find correlationsbetween the used amount of explosives, blasted volume, area and muckingwith seismic events.The result shows that localization of seismic events follows the active miningareas, but also areas with higher stresses in the numerical analysis. There areonly a few events in the southern part of the Fabian ore body which so far is anarea with no production. There are much more seismic events in the hours aftermidnight when LKAB have their production blasts.The analysis also shows that the energy tends to increase with deeper miningwhile the seismic moment tends to decrease.The different seismic indicators do not show a clear source mechanism.Hudyma & Potvin (2010) ...